Implicit Differentiation.

Calculus Level 1

Consider the function

3 y 2 + 2 x 3 = 9 x . 3y^2 + 2x^3 = 9x.

What is the value of d y d x ? \frac{ dy}{dx}?

4 2 y x 2 y \frac{4}{2y} - \frac{x^2}{y} 2 3 y x 2 y \frac{2}{3y} - \frac{x^2}{y} 3 2 x x 2 y \frac{3}{2x} - \frac{x^2}{y} 3 2 y x 2 y \frac{3}{2y} - \frac{x^2}{y}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

3 y 2 + 2 x 3 = 9 x d d x 3 y 2 + d d x 2 x 3 = d d x 9 x d d x 6 y + 6 x 2 = 9 d d x 6 y = 9 6 x 2 d d x = ( 9 6 x 2 ) 6 y d d x = 9 6 y 6 x 2 6 y d d x = 3 2 y x 2 y 3{ y }^{ 2 }+2{ x }^{ 3 }=9x\\ \frac { d }{ dx } 3{ y }^{ 2 }+\frac { d }{ dx } { 2x }^{ 3 }=\frac { d }{ dx } 9x\\ \frac { d }{ dx } 6y+6{ x }^{ 2 }=9\\ \frac { d }{ dx } 6y=9-6{ x }^{ 2 }\\ \frac { d }{ dx } =\frac { (9-6{ x }^{ 2 }) }{ 6y } \\ \frac { d }{ dx } =\frac { 9 }{ 6y } -\frac { 6{ x }^{ 2 } }{ 6y } \\ \frac { d }{ dx } =\frac { 3 }{ 2y } -\frac { { x }^{ 2 } }{ y }

Sanjeet Raria
Sep 22, 2014

Short way to imlicit differentiation, First write the equation in the form f ( x , y ) = 0 f(x,y)=0 Then d y d x = ( d f d x ) ( d f d y ) \frac{dy}{dx}=-\frac{(\frac{df}{dx})}{(\frac{df}{dy})}

(Here df/dx is partial differentiation meaning differentiation of f taking y as constant & the same goes for df/dy as well.)

Hence from our function, 3 y 2 + 2 x 3 9 x = 0 3y^2+2x^3-9x=0 d y d x = 6 x 2 9 6 y = 3 / 2 y x 2 / y \frac{dy}{dx}=-\frac{6x^2-9}{6y}=\boxed{3/2y-x^2/y}

@Marvin Kalngan I edited the problem statement for clarity. Can you review it for accuracy?

Calvin Lin Staff - 6 years, 8 months ago

3 y 2 + 2 x 3 = 9 x 3y^2+2x^3=9x

By implicit differentiation, we have

6 y d y d x + 6 x 2 = 9 6y\dfrac{dy}{dx}+6x^2=9

6 y d y d x = 9 6 x 2 6y\dfrac{dy}{dx}=9-6x^2

Dividing both sides by 6 y 6y , we have

d y d x = 9 6 x 2 6 y = 3 2 y x 2 y \dfrac{dy}{dx}=\dfrac{9-6x^2}{6y}=\dfrac{3}{2y}-\dfrac{x^2}{y}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...